FAKTOR PERUBAHAN PENDAPAT IMAM AL-SHAFI`I DARI QAWL QADIM KEPADA QAWL JADID - Ali, Abdul Karim (Jurnal Syariah, 2019)
The existence of two doctrines, qawl qadim and qawl jadid is a distinctive feature of al-Shafi`i madhhab. The former is fatwa, ijtihad or views issued by al-Shafi`i while he was in Iraq, while the latter is his fatwa, ijtihad or views when he was in Egypt. Generally, the existence of his two doctrines is due to certain differences between Iraq and Egypt in terms of time, place, custom and finding of new hadith. Therefore, the article attempts to analyse selected cases of fiqh in order to identify what leads Imam al-Shafi`i to change some of his ijtihad, fatwa and views from qawl qadim to qawl jadid.